Global variation in the assessment of psychological trauma in pregnancy - Kathryn Wall; Francesca Penner; Lindsey Wallace Goldman; Jin Young Shin; Eloise Novak; Amanda Lowell; Michèle Day; Lea Papa; Drew Wright; Soudabeh Givrad; Helena J. V. Rutherford (Cambridge Prisms: Global Mental Health)
A history of psychologically traumatic experiences can impact health outcomes for pregnant people and their infants. The perception and prevalence of traumatic experiences during pregnancy may differ by geographical region. To better understand trends in how and what kinds of psychological trauma are assessed globally, we conducted a secondary analysis on a larger systematic review examining psychological trauma measurement in pregnancy. Through a systematic literature review conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, completed between July 2021 and September 2023 using Ovid MEDLINE, Ovid EMBASE, Scopus, Web of Science, PsycInfo and Cochrane, we identified 576 research studies assessing psychological trauma during pregnancy that were conducted across nine geopolitical regions. Most of these studies took place in North America, followed by sub-Saharan Africa, Europe, Asia, the Middle East or Northern Africa, Oceania, South America, and Central America. The fewest number of studies was conducted across multiple regions. We found that most studies measuring psychological trauma in pregnancy across the nine geopolitical regions assessed interpersonal trauma, and the fewest number of studies assessed healthcare trauma. Moreover, for each type of psychological trauma assessed, the greatest number of studies was conducted in North America. We also found that Central America, Oceania, sub-Saharan Africa, Asia, Middle East or Northern Africa, Europe, and studies conducted across multiple regions had one-third or more studies that only used in-house assessments, rather than previously validated assessments of psychological trauma. The results of this review emphasize the need for regionally specific and culturally appropriate measures of psychological trauma for pregnant people, which prioritize the types of psychological trauma that are most common in a given region. Newly developed measures can be used for screening and treatment of patients using trauma-informed obstetric care.